Smoking and cognitive impairment among older persons in Malaysia - Momtaz, Yadollah Abolfathi; Ibrahim, Rahimah; Tengku Abd Hamid, Tengku Aizan; Chai, Sen Tyng (Sage Publications, 2015)
Introduction: Previous studies have shown conflicting results on the association between smoking and cognitive function. This study aims to examine the relationship of smoking with cognitive function. Methodology: Data for the study, consisting of 2553 older adults aged 60 years and older, were drawn from a nationwide household survey entitled “Determinants of Wellness among Older Malaysians: A Health Promotion Perspective” conducted in 2010. Results: Current smokers had lower rates of cognitive impairment compared to never smokers (17.4% vs 25.9%), while cognitive function in former or ex-smokers was almost similar to that of the never smokers. Findings from multiple logistic regression analysis showed that current smokers were 37% less likely to be cognitively impaired, compared to the never smokers (odds ratio [OR] = .63; 95% confidence interval [CI]: .46-.86) while controlling for potential confounders. No difference in cognitive function was observed between former smokers and never smokers (OR = .94; 95% CI: .71-1.25). Conclusion: Although the findings indicated a negative association between cigarette smoking and cognitive impairment, we are unable to conclude whether this relationship is causal or affected by other unmeasured confounding factors, especially survival bias.